2009
DOI: 10.1179/174313209x393573
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine regulates neurogenesis in ischemic mice by inhibiting NF-κB p65/p50 expression

Abstract: NF-kappaB plays a key role in regulating neuron damage and neurogenesis. This work suggests that down-regulation of NF-kappaB expression may be one of the mechanisms by which quetiapine inhibits neurogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
0
22
1
Order By: Relevance
“…Contrary to findings in preclinical studies, quetiapine did not seem to protect against hippocampal volume loss (Bi et al 2009 ;Park et al 2006). No linear correlation between mean dose and volume loss was observed and the hippocampal volume loss appeared most pronounced in the high-dose group compared to HC.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Contrary to findings in preclinical studies, quetiapine did not seem to protect against hippocampal volume loss (Bi et al 2009 ;Park et al 2006). No linear correlation between mean dose and volume loss was observed and the hippocampal volume loss appeared most pronounced in the high-dose group compared to HC.…”
Section: Discussioncontrasting
confidence: 77%
“…This has prompted the question as to whether antipsychotic compounds, and in particular SGAs, may protect against hippocampal volume loss (Angelucci et al 2000 ;Bai et al 2003 ;Halim et al 2004). In preclinical studies quetiapine has been shown to increase brain-derived neurotrophic factor (BDNF) expression (Park et al 2006 ;Xu et al 2002), to reduce neurodegeneration induced by global cerebral ischaemia (Bi et al 2009 ;Yan et al 2007), and to reverse stress-induced suppression of neurogenesis (Luo et al 2005) in hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover no increased risk of cerebrovascular events had been documented during atypical neuroleptic treatment (e.g risperidone or olanzapine) [37]. In experimental animal models of cerebral ischemia the olanzapine, risperidone, and quietapine showed evidence for neuroprotection after permanent focal cerebral ischemia [38-40]. …”
Section: Hemichorea-hemiballism Dystoniamentioning
confidence: 99%
“…[13]. Neuron-specific enolase and neuroglial mark-protein S-100 can reflect the degree of cerebral injury [46].…”
Section: Introductionmentioning
confidence: 99%